Strategies of environmental protection policies on sustainable waste management systems in Kwara and Oyo States, Nigeria - Amin, Amin; Abdullahi, Alabi; Bamidele, AbdulRasheed Hamza (Faculty of Administrative Science and Policy Studies, 2024)
The paper examined the strategies of environmental protection policies on sustainable waste management in Kwara and Oyo states in Nigeria. The study adopted Marxian Political Ecology theory. The population of this study was 11,170,478 while the sample size was 400. Out of 400 questionnaires distributed, 363 were correctly filled, retrieved and analyzed. Both primary and secondary data. SPSS version 21 was used to analyze the collected data for easy analysis. Despite growing concerns about the adverse environmental impacts of improper waste management practices, many regions and communities continue to struggle with inadequate strategies for waste disposal and recycling. It is presumably observed that there is a lack of effective strategies for the implementation of environmental protection towards sustainable waste management in Kwara and Oyo States. The study's conclusions showed that most respondents in the states of Kwara and Oyo concurred that the state has environmental conservation awareness campaigns and education initiatives. Additionally, the majority in both states concurred that the state government and NGOs collaborate on joint activities and that the dumpsite is approved. The report suggests that the governments of Kwara and Oyo states develop recycling and treatment facilities as well as more dumpsites. Priority should be given to environmentalists during the hiring, placement, and selection processes. Both States should implement landfills rather than just dumpsites, and Kwara State in particular should have an atmosphere that is supportive of private waste collectors.